Bursts of morphological and lineage diversification in modern dasyurids, a 'classic' adaptive radiation. (20th March 2018) - García-Navas, Vicente; Rodríguez-Rey, Marta; Westerman, Michael
Abstract: The Australasian marsupial family Dasyuridae exhibits one of the most spectacular species-level diversity of any marsupial group. The existence of such exceptional species and phenotypic diversity is commonly attributed to ecological opportunity (EO). According to the EO hypothesis, organisms freed from the burden of competition may undergo an initial burst in diversification and morphological evolution. Subsequently, as accessible niches become occupied, rates of diversification should slow through time. We examined the dynamics of lineage and phenotypic diversification to test whether Dasyuridae diversified in a classic adaptive radiation. We found that patterns of both lineage diversification and phenotypic (body mass) disparity exhibited an early burst as predicted by the EO model. Three historical events may have spurred this radiation: the extinction of thylacinids, the emergence of the New Guinean cordillera, and the spread of arid habitats as evidenced by the existence of phylogenetic clustering in these regions. In contrast to previous studies carried out on continent-wide systems, our results support a niche-filling scenario with an early-burst signal strong enough to be detected. This study shows that the diversification of Dasyuridae conforms fully to the postulates of the EO hypothesis and thus it constitutes a 'classic' adaptive radiation.